Perbedaan Pengaruh Terapi Murottal Selama 15 Menit Dan 25 Menit Terhadap Penurunan Skala Nyeri Pada Pasien Kanker Pascabedah - Nani Sri Mulyani; Iwan Purnawan; Arif Setyo Upoyo (Journal of Bionursing, 2019)
Background: Surgery in cancer patients can cause pain. Pain can be overcome through pharmacological and non-pharmacological therapy. One of non-pharmacological therapies to reduce pain is murottal therapy because it can stimulate extraction of ?-endorphin.Objective: This research aimed to determine the difference in effect of murottal therapy for 15 minutes and 25 minutes on reduction of pain scale in post-surgery cancer patients.Method: This research used quasi experimental research design with non-randomized pretest-posttest with control group design approach. The sampling in this research used consecutive sampling. The sample size in this research was 30 respondents. This amount was divided into 2 groups: 15 respondents of 15 minutes murottal therapy group and 15 respondents of 25 minutes murottal therapy group. Data analysis used the Wilcoxon and Mann Whitney test.Result: The majority of respondents aged 40-60 years old, female, and suffering from breast cancer. The result indicated that there was a significant difference in the pain scale in 15 minutes group (p=0.002) and 25 minutes group (p=0.000). But, there was no significant difference in the reduction of pain scale in both groups (p=0.167). However, the average reduction of pain scale in 25 minutes group was greater (2.00±0.66) than 15 minutes group (1.53±1.06).Conclusion: Murottal therapies for 15 minutes and 25 minutes were equally effective for reducing pain in post-surgery cancer patients.